Redescription of Protanura papillata Cassagnau & Delamare Deboutteville, 1955 (Collembola, Neanuridae, Neanurinae), with new records from Middle East, and with supplemented diagnosis and key to the genus - Smolis, Adrian; Skarżyński, Dariusz; Kahrarian, Morteza; Kaprus, Ighor J. (Zootaxa, 2016)
The poorly known Neanurini genus Protanura is rediagnosed and briefly compared with Lathriopyga. Protanura papillata Cassagnau & Delamare Deboutteville, 1955, known to date only from Lebanon, is redescribed based on the lectotype and new extensive material from Middle East.